Developing Best Analytical Material Application Based on Android in Reading Skill for Eleventh Grade Students - Afidah, Nurul; Kumalasari, Evy; Agustina, Ulfa Wulan (APPLICATION: Applied science in Learning Research, 2023)
The objective of this research is developing BACA (Best Analytical Material Application) as a learning media based on android using iSpring Suite 10 in reading skills for 11th Grade Islamic Senior High School of (MA) Maâ€™arif 1 Jombang. The research method of this study is Research & Development (R&D) and the researcher choose ADDIE model in developing the product. There are 5 stages of development using ADDIE model: Analyze, Design, Development, Implementation, and Evaluation. The researcher used validation sheet to evaluate the quality of BACA learning media. The result of media validation is 3.5. Moreover, the result of material validation the researcher got 3.4, in other word it was a very good category. Meanwhile, the result of the implementation product obtained from the student response questionnaire were 91%. Based on these data, it can be concluded that BACA (Best Analytical Material Application) based on android for 11th Grade Islamic Senior High School of (MA) Maâ€™arif 1 Jombang has good quality and can be used as a learning media in real class. Â